LET spectra behind high-density titanium and stainless steel hip implants irradiated with a therapeutic proton beam. (March 2018) - Oancea, C.; Ambrožová, I.; Popescu, A.I.; Mytsin, G.; Vondráček, V.; Davídková, M.
Abstract: A well-known shortcoming of radiotherapy is the lack of information regarding the effect that metallic implants, located near the area of interest, have on the dose distribution in the target volume. In this work, a scanned proton pencil beam was applied to hip implant phantoms to evaluate Linear Energy Transfer (LET) and to study the secondary particles produced close to the implant. Using two different materials that are in standard use in hip implant production worldwide, phantoms with thicknesses of 2, 5, 10, 15, and 20 mm were manufactured. The first phantom type consists of a titanium (Ti) alloy, while the second is composed of a stainless steel (SS) alloy. Both phantoms were irradiated at various energies. Solid - state nuclear track etched detectors (TEDs) have been used to determine LET spectra of primary protons and secondary particles, both behind the implants and near their edges. The results indicate that LET spectra behind particular materials of different thicknesses do not differ from qualitative point of view. When we compared LET spectra of Ti and SS materials of the same thickness, more particles with LET, below 20 keV/μm, were detected behind the SS phantom. At the border of a phantom made from 20 mm metallic alloy, there was an accumulation of tracks, resulting from the scattering of the protons in the material. The dosimetric information, obtained in the experimental study, can be further applied either for benchmarking treatment planning systems or for biological dose calculations. Highlights: Study of LET spectra behind metallic hip implants. Modified particle fluences at the border of metal and plastic materials. Changes in absorbed dose at the border between implants and plastic material.